Analysis of the Impact of Science-Fiction Films and Science-Fictions Books on the Environmental Literacy of 7th-Grade Students - Çakir Şik, Çiğdem; Fatma Önen Öztürk (Science Insights Education Frontiers, 2025)
This study aimed to examine the impact of science-fiction films and books on the environmental literacy of 7th-grade students. The study was conducted during the initial half of the 2022-2023 academic year, involving 63 seventh-grade students from a secondary school in the Ümraniye district of Istanbul, with 21 students in each of the three classes, which exhibited no significant differences among them. One class served as the control group, while the other two constituted the experimental group. Classical methods and techniques were utilized in the control group, while one experimental group engaged with three science fiction movies and the other group utilized three science fiction books and a curriculum. The study employed a mixed design. In the six-week study, the “Environmental Literacy Scale” was used as both a pretest and posttest for quantitative data collection. The quantitative data acquired from this test were analyzed using the SPSS program. The data revealed significant differences in certain sub-problems of the research, as assessed by the sub-dimensions of environmental literacy in the Experiment 1 and Experiment 2 groups. The cognitive skills test and semi-structured interview form were assessed qualitatively. Content analysis was employed to examine qualitative data. The responses provided to the qualitative measurement instruments were converted into codes and themes, and their frequency levels were assessed. The results of the responses and quantitative data coincide. The study suggests that incorporating science-fiction movies and books into science education enhances students’ environmental literacy.